Impact Analysis of a Flexible Air Transportation System - Atasoy, Bilge; Salani, Matteo; Bierlaire, Michel; Leonardi, Claudio (European Journal of Transport and Infrastructure Research, 2013)
The paper provides analytical evidence of the added-value of flexibility for air transportation systems. More specifically, the impact of a new innovative modular aircraft on the operations of an airline is deeply analyzed. The impact analysis is carried out with an integrated schedule planning model which presents a combination of appropriate optimization and behavioral modeling methodologies. The results show that the flexible system uses the transportation capacity more efficiently by carrying more passengers with less overall capacity. Moreover, it is observed that the flexible system deals better with insufficient transportation capacity. Furthermore, the scheduling decisions are robust to the estimated cost figures of the new system. For the analyzed range of costs, it is always carrying more passengers with less allocated capacity compared to a standard system.